The Net in a Fuzzy Soft Topological Space and Its Applications - Rui Gao; Jianrong Wu (Journal of Mathematics)
In this paper, the fuzzy soft net is explored to study the properties of a fuzzy soft topological space. Some important results about the closure, separation, and compactness are obtained. It is demonstrated that the net is a powerful tool for studying fuzzy soft topological spaces.